Proton Therapy Current Status and Future Directions - FitzGerald, Thomas J.; Bishop-Jodoin, Maryann (IntechOpen, 2021)
Over the past twenty-five years, proton therapy has become more prominent worldwide. It is an important component of clinical radiation therapy for both adult and pediatric clinical care. Due to the inherent ability of protons to spare normal tissue, protons will continue to develop and become increasingly important in radiation oncology. As such, Proton Therapy - Current Status and Future Directions reviews many aspects of proton care including the application of protons in modern clinical trials. It also reviews problems associated with the migration of proton care worldwide and examines the future direction of proton care. This project was created by colleagues at IntechOpen and was carefully managed by Romina Rovan. It has been a privilege to help coordinate the text and chapters designed to acknowledge the history, footprint, and growing interest of proton care worldwide. Proton management is now embedded in the clinical trials process. In pediatric care, proton delivery is embedded with photons for the management of pediatric malignancies and adult groups have initiated proton-specific clinical trials. A proton registry has been established and outcomes are under evaluation. Due to the inherent ability of protons to spare normal tissue, protons will continue to develop and become increasingly important in radiation oncology.